Islamic Social Reporting (ISR) Disclosure: Financial Performance Factor - Dewita Puspawati; Rita Wijayanti; Novel Idris Abas (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2020)
The development of ISR in Indonesia is still relatively slow. Several previous studies have proven that all the Sharia banks in the research sample have not achieved 100% implementation and disclosure of ISR. This study uses several independent variables, namely company size, profitability, liquidity, leverage, sharia supervisory board, audit committee, board of commisioners. Based on the results of the previous research, there is still a research gap that occurs. This study used a sample of 13 Sharia Commercial Banks in 2016-2019. The results show that the variables of company size, profitability, liquidity, leverage, and the board of commissioners affect the level of ISR disclosure. Meanwhile, the sharia supervisory board and audit committee did not affect the level of ISR disclosure.